XÁC ĐỊNH ACETAMIPRID BẰNG PHƯƠNG PHÁP QUANG HỌC SỬ DỤNG DUNG DỊCH NANO VÀNG ĐƯỢC ỔN ĐỊNH BẰNG POLYDIALLYLDIMETHYLAMMONI CLORUA - Lê, Thị Thảo; Trần, Ngọc Bích; Vũ, Thị Vinh; Nguyễn, Quang Khánh; Phạm, Gia Bách; Phạm, Thị Ngọc Mai (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
DETERMINATION OF ACETAMIPRID BY SPECTROPHOTOMETRIC METHOD USING GOLD NANOPARTICLES STABILIZED WITH POLYDIALLYLDIMETHYLAMMONIUM CHLORIDEOn this research, the development of a simple, cost-efective and highly sensitive spectrophotometric method for acetamiprid detection based on the localized surface plasmon resonance of polydiallyldimethylammonium chloride-stabilized gold nanoparticles. By naked eyes, one can detect acetamiprid by the visual change of gold solution color from red to purple, corresponding to the shift of maximum absorbance wavelength in the UV-Vis spectrum. Quantification of acetamiprid is possible through a linear relationship between the maximum absorbance wavelength and the acetamiprid concentrations in the range of 8×10-8 - 2×10-6 M. Under the optimum conditions including pH 5, NaCl concentration of 0.02 M and incubation time 20 min, the present method has high precision (RSD < 5%), very low limit of detection (LOD) of 2.7×10-8 M, limit of quantification (LOQ) of 8.2×10-8 M. This method has been successfully applied to determine acetamiprid in several pesticide samples and vegetable samples. The measurement results of acetamiprid in the pesticide samples of the research method with the HPLC-UV method showed a difference of < 2%, while for the vegetable sample, the difference between the research method and the LC-MS/method method/ MS < 5% shows that the method has high accuracy and reliability.